Urea treatment effect on straw of different paddy cultivars grown in Tarai region of Uttarakhand - PANDEY, POONAM; KUMAR, ANIL (The Indian Journal of Animal Sciences, 2011)
The present experiment was planned to study the response of urea treatment in different paddy straw cultivars. In study, samples of 18 cultivars were collected and half of the sample was treated with 4% urea (35% moisture) and kept for 4 weeks in air-tight polythene bags. Chemical composition and degradability of these paddy straw cultivars for DM, NDF, ADF, CP, HC and cellulose content were determined by using nylon bag technique. Three rumen fistulated animals were used to incubate nylon bags for 72 h. These animals were fed with green oat ad lib. just after feeding of concentrate mixture prepared from 30 parts of GNC, 32 parts of deoiled rice bran, 35 parts of wheat grain, 2 parts of mineral mixture and 1 part of common salt. After urea treatment, the mean CP content increased significantly while DM, NDF, ADF, HC and cellulose content decreased significantly. Significant urea treatment effect was seen as enhanced degradability of all parameters. Some low nutritive value paddy straw cultivars responded more due to urea treatment in comparison to the paddy straw cultivars of higher nutritive value.Â